Steroids from the Leave of Persicaria perfoliata (L.) H. Gross (Bangladesh Pharmaceutical Journal, 2019)
β-sitosterol (1) and β-sitosterol-D-glucoside (2) were isolated from the dichloromethane soluble fraction of a methanol extract of the leave of Persicaria perfoliata. The crude fraction was subjected to antimicrobial screening and brine shrimp lethality bioassay, where moderate antimicrobial activity was observed against most of the test organisms was seen. The hexane soluble fraction also displayed significant cytotoxic activity with LC50 0.64 μg/ml in brine shrimp lethality bioassay. This is the first report of occurrence of these compounds from this plant.Bangladesh Pharmaceutical Journal 22(2): 224-227, 2019